An optimum treatment for waste electronic home appliance in remote area: The case of Kinmen, Taiwan. (15th April 2019) - Lin, Hsin-Tien; Nakajima, Kenichi; Yamasue, Eiji; Ishihara, Keiichi N.
Highlights: Local pre-processing can reduce the treatment cost of e-waste for remote area. Characteristics of e-waste affects the cost reduction of local pre-processing. Labor cost and transportation distance are main factors for cost effectiveness. Abstract: An optimum treatment system for the waste electronic home appliance in remote area by local pre-processing and outsourcing post-processing is proposed. The cost reduction potential of the proposed treatment system is presented for main four types of electronic home appliances by the case study of Kinmen, Taiwan. Implementation of local pre-processing in Kinmen, Taiwan can provide 42, 54, 32, and 41 TWD unit cost reduction for television, washing machine, refrigerator, and air conditioner, respectively, comparing to the current treatment system. The different treatment characteristics according to the type of the appliances are the major factors for the applicability and cost reduction potential of the local pre-processing system. The application of this system to other cases is presented by sensitivity analysis with relative labor cost and transportation distance as the parameters. The results and the analysis process can be applied to the domestic systems with regions without recycling facilities, and also the international systems under the extended producer responsibility concept to take back the products for recycling.